Hookworm infection associates with a vaginal Type 1/Type 2 immune signature and increased HPV load - Omondi, Millicent A.; Kamassa, Eya H.; Katawa, Gnatoulma; Tchopba, Christèle N.; Vogelbusch, Celina; Parcina, Marijo; Tchadié, Edlom P.; Amessoudji, Oukoe M.; Arndts, Kathrin; Karou, Simplice D.; Ameyapoh, Yaovi; Kolou, Malewé; et al. (Frontiers in Immunology, 2022)
Helminth infection-driven changes to immunity in the female reproductive tract (FRT) is an immune axis that is currently understudied but can have major implications for the control of FRT infections. Here we address how human hookworm infection associates with vaginal immune profile and risk of Human papillomavirus (HPV) infection. Stool, blood, cervical swabs and vaginal flushes were collected from women from the Central region of Togo to screen for hookworms (Ancylostoma duodenale) and high carcinogenic risk HPV types, via Kato Katz and PCR, respectively. Cytokine, chemokine and immunoglobulin levels were analysed in cervicovaginal lavages and plasma samples. A pronounced mixed Type 1/Type 2 immune response was detected in the vaginal fluids of women with hookworm infection and this immune signature was a notable feature in hookworm-HPV co-infected women. Moreover, hookworm infection is positively associated with increased risk and load of HPV infection. These findings highlight helminth infection as a significant risk factor for acquiring a sexually transmitted viral infection and potentially raising the risk of subsequent pathology.